Evaluasi Pemilihan Supplier Komponen Sistem Pneumatik dalam Manajemen Pemeliharaan dengan Menggunakan Analytical Hierarchy Process pada Pabrik Kemasan Kertas - Ramadhania, Sherin; Suroso, Muhammad Suryo Panotogomo Abi; Permata, Nia Sastra (Politeknik Negeri Batam, 2024)
To ensure the continuity of the production process, it is essential for the company to focus on maintenance management, particularly in selecting high-quality pneumatic system components with a long lifespan. This study aims to determine the criteria and weights for choosing suppliers of these components in a paper packaging manufacturing. The supplier alternatives evaluated are PT. SMCAI, PT. FI, and PT. RMW, using the Analytical Hierarchy Process (AHP). The analysis of the four criteria reveals the following weights: cost (0.46), quality (0.23), service (0.16), and delivery (0.15). Based on these evaluations, PT. SMCAI ranks highest with a weight of 0.41, followed by PT. FI at 0.40, and PT. RMW with the lowest weight of 0.19. These results guide the company in selecting the most suitable supplier to maintain smooth production operations.